(3OaY GdeVGQ GdcdjI Yf GdCHOGf GdEfSGfjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3hHYO aEf GdTjN GdLdjd CHG GdMSf CMeO Hf eMeO GdSgdi , hgh ef oYQa HYdh GdgeI CeQfi ajeG CeQ ef GdChGeQ GdMcjeI Cf CYed cJGHkG ai OaY GdeVGQ GdcdjI ddCHOGf GdEfSGfjI s
(3BNQgG (B:s
(3hGeG efY GdESgGd Ch JOHjQ ef de kjSgd aEfg ehLhO aj GdcJH , hdjcf gPG cGajkG ai ZQVfG hGdMeO dhGgH GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B225 - (3U(B250s
(3GfXQ agQS GdWH HQbe (B120s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs